Bibliometric Analysis of Bronchopulmonary Dysplasia in Extremely Premature Infants in the Web of Science Database Using CiteSpace Software - Zhou, Qin; Kong, Hai-Bo; He, Bao-Mei; Zhou, Su-Ya (Frontiers in Pediatrics, 2021)
Objectives: To review the literature related to bronchopulmonary dysplasia in extremely premature infants, summarize research hotspots, and report trends. Methods: Relevant articles from 2008 to 2020 were retrieved from the Web of Science Core Collection database, and we extracted the following data: title, abstract, year, keywords, author, organization, journal and cited literature. We downloaded the data into CiteSpace (version 5.7.R3) to summarize countries, institutions, journals, and authors. We visualized the data with a knowledge map, collaborative network analysis, cluster analysis, and burst keyword analysis. Results: We identified 610 articles on bronchopulmonary dysplasia in extremely premature infants. The United States had the most articles on this topic (302 articles), followed by Canada (49 articles) and Germany (44 articles). The top three institutions, high-yield journals, and authors were all from the United States. The most common keywords were neurodevelopmental disorders, active perinatal care, mechanical ventilation, inflammation, pulmonary hypertension, low-dose hydrocortisone, development, and patent ductus arteriosus. Conclusions: This study illustrates the trends and frontiers in the study of bronchopulmonary dysplasia in extremely premature infants. The current hot issues are to identify the high-risk factors of bronchopulmonary dysplasia in extremely premature infants, reasonable hormone use, new cell therapy, and management of complications.